Balinese Flashcard as English Learning Material in Teaching Vocabulary - Diah Permata Sari AR, Gusti Ayu Putu (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
English as a foreign language challenges the non-native speaker to develop their ability in improving four essential English skills. Furthermore, Bali as a famous tourism destination that is rich in cultures and traditions, requires Balinese, especially students in Communication Study Program to master both Balinese and English in order to be able to describe the related terms in English. To gain that purposes, the lecturer can implement learning media namely Balinese Flashcard for university students. This study aimed at describing Balinese Flashcard as English learning media at Communication Studies Program, STAHN Mpu Kuturan Singaraja. The Balinese Flashcard contained several vocabularies and written in Balinese-English. The research was designed using qualitative approach. The subject was students in the fourth semester of Communication Studies Program, STAHN Mpu Kuturan Singaraja. The data were collected through observation, interview, and questionnaire. The data were analyzed qualitatively. Overall, the use of Balinese flashcards in English learning can have many positive implications for students. The result showed that Balinese Flashcard effectively enriched English vocabulary in describing Balinese culture and tradition. Furthermore, using Balinese Flashcard can stimulate the students to build their ideas, encourage creativity, and evolve themselves in English learning. By incorporating flashcards into language learning activities, the lecturer can help the students to improve their English language proficiency and make learning more meaningful and enjoyable.